Assessment of the Acceptable Range of Lips and Chin Position in Two Different Geographical Zones of Iran among Laypersons - Farzaneh Golfeshan; Athar Nasseri Mojarad; Ahmadreza Sardarian (Journal of Dentistry, 2024)
Statement of the Problem: The position of the chin and lips are important components in the lower third of the face and can be changed by orthodontic treatment. It seems that factors such as diversity in culture, ethnicity, and place of residence are among the factors affecting people's perception of beauty. Iran, as a vast country, contains different ethnicities and cultures, and of course, it is not exempt from this point of view.Purpose: Our purpose of conducting this study is to investigate the impact of the difference in living environment and culture on people's aesthetic perception. Orthodontists and oral surgeons can use these data to choose the best treatment plan for the patients according to their geographical zones.Material and Method: A descriptive cross-sectional study was conducted to evaluate the perception of lips and chin position. A series of 25 profile images were prepared in 5 sets. Each set contained 5 profile images. Northern and Southern lay people and orthodontists were asked to evaluate the profile series of each set in 1 session and score them from 1 to 5: 1, very unattractive; 2, unattractive; 3, neither attractive nor unattractive; 4, attractive; or 5, very attractive. Results: 652 participants in 3 groups, including 16 orthodontists (10 men and 6 women), 318 lay people of the North of Iran (172 men and 138 women), and 318 lay people of the South of Iran (175 men and 139 women) participated in this study. Regardless of the chin position, normal lip position and slight changes of that (both in protruded and retruded position) were more favorable for all three groups. The images with moderately retruded lips were scored as the least attractive by all three groups and orthodontist gave the lowest score to these profiles. Southern people could better tolerate moderately retruded lips than other two groups. In the fifth series, orthodontists preferred slightly and moderately protruded lips in comparison to other two groups of laypeople.Conclusion: Regardless of the chin position, normal and slightly (-2mm to +2mm) protruded and retruded lips were more favorable in all three groups. Southern people could better tolerate moderately retruded lips than the two other groups.